Study of the oxidative stability of oils vegetables for production of Biodiesel - R Melo, Marco Aurélio; M F Melo, Maria Andreia; Silva, Everton Vieira; Carvalho Filho, José Rodrigues; Souza, Antonio Gouveia (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2014)
Biodiesel is technological and estrategical Brazilian oportunity once this country has abundant vegetable species which oils are extracted to produce this biofuel. Oleaginous viability depends on its technical, economical and social-environmental competitiviness. Fatty acid variety determines its thermal and oxidative stability, mainly polyunsaturated ones. In this point of view, this papers aims evaluate oxidative stability and resistence to thermal decomposition of pequi, buriti and macauba oils. These fatty acids profiles are in agreement with literature data. Comparing thermal and oxidative stability of these oils, it can be seen pequi oil is more easily to oxidate than buriti and macauba oils when PetroOXY and Rancimat methods are employed.